Pseudocoordination, Serial Verb Constructions and Multi-Verb Predicates: The relationship between form and structure - Ross, Daniel (Zenodo, 2021)
What is pseudocoordination? What are the implications for syntactic theory? This dissertation approaches these questions from the perspective of linguistic typology and syntactic theory. Verbal pseudocoordination like go and get or try and do is an under-studied phenomenon even in English but especially in languages around the world. In some ways resembling coordination, in others subordination, the mixed properties of these constructions introduce substantive questions for language comparison and theoretical analysis, given the variety of ways in which languages render similar structural relationships and dependencies. This dissertation makes three broad contributions to linguistic research. First, the results of a worldwide, balanced sample of 325 languages, as well as smaller samples of creoles and signed languages, provide the distribution and typology of pseudocoordination and other multi-verb constructions, supplemented by the appendix listing these features for each language and a comprehensive bibliography. Second, the unusual morphosyntactic restrictions of the English try and construction are documented in detail, along with parallels in Faroese, and shown to require augmented methods for syntactic analysis. Third, the diversity of multi-verb constructions and other theoretically challenging constructions support the proposal of an approach to syntactic theory mixing insights from Generative Grammar and Construction Grammar. This research will be relevant to typologists studying mult-verb constructions and related phenomena, and to syntacticians interested in the architecture of syntactic theory. The typological surveys of the first five chapters are independent of theoretical perspective, while the theoretical considerations reach beyond multi-verb constructions to how linguists approach syntax in general and suggest pathways for inclusive research agendas that are mutually beneficial for researchers working with different theoretical frameworks. Overall, I draw connections between research traditions to advance our understanding of human languages. Chapter 1 provides background on pseudocoordination and the methodology for the cross-linguistic survey. Coordination strategies in the sample languages are also surveyed. Chapter 2 is a worldwide survey of pseudocoordination, including but not limited to the sample languages. The phenomenon is more widespread than assumed in previous literature. The typology and grammaticalization of these constructions are also discussed. Chapter 3 surveys three clause-combining strategies: converbs, Switch-Reference, and para-hypotaxis. Their typology is discussed, including usage in multi-verb constructions. Chapter 4 provides a comprehensive review of the definition of Serial Verb Constructions and then surveys their distribution. A parallel is drawn between these and other multi-verb constructions with monoclausal properties, and their analysis as Multi-Verb Predicates clarifies some controversial aspects of the definition of Serial Verb Constructions, while unifying the analysis of similar pseudocoordination, converb and other construction types, which differ only in form. It is emphasized that typological comparisons are facilitated by avoiding definitions that arbitrarily mix formal and functional criteria. Chapter 5 turns to a particular semantic domain to illustrate variation in the realization of the grammatical category of Associated Motion. First, the worldwide distribution of Associated Motion and Directional morphology on verbs is surveyed to establish a typology. Second, the functional equivalence and similar typology of Multi-Verb Predicates is demonstrated. Chapter 6 presents an analysis of a specific construction in English, try and pseudocoordination, with a focus on the unusual morphosyntactic restriction that neither verb in the construction may be inflected: I try and write clearly vs. *He tries and write(s)… . The chapter thoroughly documents the construction in English, including its historical development, dialectal variation and acquisition, and an unsual morphological rule is shown to be necessary to explain the restricted distribution. In contrast to Multi-Verb Predicate pseudocoordination that was the focus of previous chapters, this is a complementation construction similar to infinitives but with an inflectional parallelism dependency between the two verbs. Chapter 7 investigates a similar construction in Faroese, supported by original data gathered in the Faroe Islands. The Faroese ‘try and’ construction is shown to have developed for some speakers a similar restriction to English try and pseudocoordination, in that both verbs must have inflection that looks like an infinitive, thus allowing plural present-tense usage. Chapter 8 takes a broad theoretical perspective on the relationship between linear form and underlying structure in syntatic theory. I examine relevant contributions from Generative Grammar and Construction Grammar, theories which are not mutually exclusive but provide answers to different questions. The streamlined architecture of the Minimalist Program provides a foundation for structural relationships and dependencies, while Constructions can be used to explain variation and unusual properties of the forms we pronounce.